Bardet-Biedl Syndrome: A Case Report (BIRDEM Medical Journal, 2018)
Bardet-Beidl syndrome is a rare autosomal recessive disorder having heterogeneous clinical manifestations including rod-cone dystrophy, polydactyly, obesity, learning difficulties, development delay, speech deficit, diabetes mellitus, congenital heart disease etc. Most of these symptoms are not present at birth but appear and progressively worsen during the first and second decades of life. The combined occurrence of diabetes mellitus and retinitis pigmentosa is rare. Here, we present such a case.Birdem Med J 2018; 8(2): 184-186